Saúde mental e trabalho na assistência social: vivências de sofrimento psíquico e estratégias de defesa dos(as) servidores(as) públicos(as) municipais da FUNPAPA em Belém/PA - MENDES, Andréa de Barros (Universidade Federal do Pará, 2013)
Inserted in the context of relationships established between mental health and work, this study aims to analyze the experiences of psychological distress of servers responsible for performing the activities of network social protection the FUNPAPA, emphasizing the development of strategies to accomplish their work in order to place themselves under the "normality". Guided on the contributions of the psychodynamics of work and references from the field of the health of the workers, the theoretical and methodological focus of this research is a qualitative approach, which data collection involved semi-structured interviews and participant observation. Data analysis, performed using the technique of content analysis, pointed out aspects related to working conditions and work organization acting as triggers of experiences of psychological distress, which are expressed in anxiety, dissatisfaction, fear, boredom, disgust, among other manifestations. The aspects related to poor working conditions that trigger the mental suffering of FUNPAPA servers are: physical space without the need to adapt to meet users' obsolete equipment and / or malfunction, scale vehicles irregular and unhealthy environmental conditions due to constant infiltration. As constituent elements of work organization that act as determinants of psychological distress experienced by servers FUNPAPA can cite: the customer service, professional training inadequate to their work, evaluating performance, lack of social recognition, the reduced quantitative server, the network socioassistencial deficit and the feeling of helplessness against the limits of social assistance. To deal with the experiences of psychological distress in order to prevent disease and madness these servers adopt defensive strategies of protection, including: rationalization, religion, bonds of trust and solidarity, absenteeism, the anticipation of the holidays, investment in activities outside the workday, the itinerant work in the community and the search for alternative solutions to make the physical environment as friendly as possible. Thus, the structure of this work includes three parts: the reference empirical and the theoretical discussion of the results, respectively. Finally, in conclusion, points out some notes to support a proposal for mental health promotion at work.